Beispiel Nr: 07
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 4 x -5 y =43\\ -3 x -7 y = 0 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 4 x -5 y =43\\ II \qquad -3 x -7 y = 0 \\ \text{I nach y auflösen}\\ 4 x -5 y =43 \\ 4 x -5 y =43 \qquad /-4 x\\ -5 y =43 -4 x \qquad /:\left(-5\right) \\ y =-8\frac{3}{5} +\frac{4}{5} x \\ \text{II nach y auflösen}\\ -3 x -7 y =0 \\ -3 x -7 y =0 \qquad /+3 x\\ -7 y =0 +3 x \qquad /:\left(-7\right) \\ y =0 -\frac{3}{7} x \\ \text{I = II}\\ -8\frac{3}{5} +\frac{4}{5} x =0 -\frac{3}{7} x \qquad /-\frac{4}{5} x /-0 \\ -8\frac{3}{5}-0 =-\frac{3}{7} x -\frac{4}{5} x \\ -8\frac{3}{5} =-1\frac{8}{35} x \qquad /:\left(-1\frac{8}{35}\right) \\ x=7 \\ \text{x in I}\\ y =-8\frac{3}{5} +\frac{4}{5} \cdot 7 \\ y=-3 \\ L=\{7/-3\} \end{array} & \begin{array}{l} I \qquad 4 x -5 y =43\\ II \qquad -3 x -7 y = 0 \\ \text{I nach x auflösen}\\ 4 x -5 y =43 \\ 4 x -5 y =43 \qquad /+5 y\\ 4 x =43 +5 y \qquad /:4 \\ x =10\frac{3}{4} +1\frac{1}{4} y \\ \text{II nach x auflösen}\\ -3 x -7 y =0 \\ -3 x -7 y =0 \qquad /+7 y\\ -3 x =0 +7 y \qquad /:\left(-3\right) \\ x =0 -2\frac{1}{3} y \\ \text{I = II}\\ 10\frac{3}{4} +1\frac{1}{4} y =0 -2\frac{1}{3} y \qquad /-1\frac{1}{4} y /-0 \\ 10\frac{3}{4}-0 =-2\frac{1}{3} y -1\frac{1}{4} y \\ 10\frac{3}{4} =-3\frac{7}{12} y \qquad /:\left(-3\frac{7}{12}\right) \\ y=-3 \\ \text{y in I}\\ x =10\frac{3}{4} +1\frac{1}{4} \cdot -3 \\ x=7 \\ L=\{7/-3\} \end{array} \end{array} $